PENGETAHUAN, SIKAP, DAN DUKUNGAN KELUARGA DENGAN KETEPATAN PEMBERIAN MP-ASI - Suci Parandari; Muslimin Muslimin; Hajrah Hajrah; Ali Imran; Adriyani Adam (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : Complementary feeding is a solid and nutrient dense foods with complete contain given to infants from 6 months of age after exclusively breastfed to achieve optimal growth and development. Complementary feeding is given from 6-24 months and must be done completely in accordance with the abilities of the baby and child. Providing sufficient Complementary feeding in terms of quality and importance for physical growth and increased intelligence increases during this period.Objectives : The aim of this study was to determine the relationship between knowledge levels, mother's attitudes, family support with accordance of complementary feeding.Methods : This research was conducted in the working area of Kampili Health Center Kabupaten Gowa. The type of research was analytical research using a cross-sectional approach. sample techniques using purposive sampling. The sample in this study were 70 mothers who have toddlers aged 6-24 months.Results : Based on the research results by using chi-square test with significance level α = 0.05. The statistical test results obtained a level of knowledge p = 0.023, maternal attitudes p = 0.017, family support p = 0.027 with the accordance of complementary feeding.Conclusions : The conclusion was that there was a correlation between the level of knowledge, mother's attitude and family support with the accordance of complementary feeding assistance in the work area of the Kampili Gowa Health Center. It is expected to provide exclusive breastfeeding for 6 months to infants and provide complementary feeding for breastfeeding at the age of 6 months and above and for health workers to improve communication, information and education (IEC) programs, especially for pregnant women and those with babies. Latar Belakang : Makanan pendamping ASI merupakan makanan padat dengan kandungan gizi yang lengkap diberikan kepada bayi sejak usia 6 bulan setelah pemberian ASI eksklusif untuk mencapai pertumbuhan dan perkembangan yang optimal. Makanan pendamping ASI diberikan mulai usia 6-24 bulan dan harus diberikan secara lengkap sesuai dengan kemampuan bayi dan anak. Pemberian Makanan Pendamping ASI dengan kualitas yang baik sangat penting untuk menunjang pertumbuhan fisik dan peningkatan kecerdasan yang meningkat selama periode ini.Tujuan : Penelitian ini bertujuan untuk mengetahui hubungan tingkat pengetahuan, sikap Ibu, dukungan keluarga dengan ketepatan pemberian MP-ASI.Metode : Penelitian ini dilakukan di wilayah kerja Puskesmas Kampili Gowa. Jenis penelitian yang digunakan adalah study analitik dengan pendekatan cros-secsional. Teknik pengambilan sampel mengunakan purposive sampling. Sampel dalam penelitian ini adalah 70 orang ibu yang memiliki balita umur 6-24 bulan.Hasil : Berdasarkan hasil penelitian dengan mengunakan uji chi-square dengan tingkat kemaknaan α = 0,05%.Hasil uji statistik diperoleh tingkat pengetahuan nilai p = 0,023, sikap ibu p = 0,017, dukungan keluarga p = 0,027 dengan ketepatan pemberian MP-ASI.Kesimpulan : Ada hubugan tingkat pengetahuan, sikap ibu dan dukungan keluarga dengan ketepatan pemberian MP-ASI di wilayah kerja Puskesmas Kampili Gowa. Diharapkan memberikan ASI ekslusif selama 6 bulan kepada bayi dan memberikan makanan pendamping ASI saat usia 6 bulan keatas dan kepada petugas kesehatan agar untuk lebih mengintensifkan kegiatan sosialisasi, informasi dan edukasi khususnya pada ibu-ibu hamil maupun ibu balita